2022
DOI: 10.1177/08850666221075568
|View full text |Cite
|
Sign up to set email alerts
|

Patients Surviving Critical COVID-19 have Impairments in Dual-task Performance Related to Post-intensive Care Syndrome

Abstract: Objective The purpose was to examine Dual Task (DT) performance in patients surviving severe and critical COVID-19 compared to patients with chronic lung disease (CLD). Secondarily, we aimed to determine the psychometric properties of the Timed Up and Go (TUG) test in patients surviving COVID-19. Design Prospective, cross-sectional, observational study. Setting Academic medical center within United States. Patients Ninety-two patients including 36 survivors of critical COVID-19 that required mechanical ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…Our long-term findings are quite like those reported from others, showing slight or no dependency in basic activities of daily living [29], and good mobility performances [30][31][32]. Our sample also showed TUG performances better than those detected in participants recovering from severe or critical COVID-19 [33].…”
Section: Discussionsupporting
confidence: 89%
“…Our long-term findings are quite like those reported from others, showing slight or no dependency in basic activities of daily living [29], and good mobility performances [30][31][32]. Our sample also showed TUG performances better than those detected in participants recovering from severe or critical COVID-19 [33].…”
Section: Discussionsupporting
confidence: 89%
“…Until now, there has been no study that focused on the comparison of dual-task performance of PwCOVID with that of HS. Therefore, in order to calculate our sample size, we relied on the single study that investigated the dual-task performance of PwCOVID, even if it compared PwCOVID with those with chronic lung disease [ 31 ]. Nevertheless, we are aware that this choice has led to a small overestimation of the sample, since the expected difference between HS and PwCOVID should be greater than that between chronic lung disease and PWCOVID [ 45 ].…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Specifically, Morelli et al [ 31 ], in their assessment of DT performance during the TUG test in PwCOVID, found a difference of 3.8 ± 5.2 s between individuals with COVID-19 vs. those with chronic lung disease. This corresponds to a Cohen’s d effect size of about 0.7.…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations